2006
DOI: 10.1615/jlongtermeffmedimplants.v16.i6.10
|View full text |Cite
|
Sign up to set email alerts
|

Surface Finish Mechanics Explain Different Clinical Survivorship of Cemented Femoral Stems for Total Hip Arthroplasty

Abstract: The ability of bone cement to adhere to the implant surface is dependent on the surface finish. Stems with a rough surface finish require greater force to disrupt their interface with the cement than do stems with a smooth or polished surface. However, if micromotion occurs at the cement-metal interface, the fretting of a smoother surface implant results in less cement and metallic abrasion than an implant with a rough surface finish. Today, surgeons implant femoral stems with a wide variety of surface finish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
12

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 0 publications
0
5
0
12
Order By: Relevance
“…However, long-term follow-up studies on the cemented rough stems clearly revealed a significantly higher loosening and revision rate than that of polished stems. [4][5][6][7][8][9] This contradiction between biomechanical theory and clinical observation is yet to be resolved.…”
Section: Introductionmentioning
confidence: 99%
“…However, long-term follow-up studies on the cemented rough stems clearly revealed a significantly higher loosening and revision rate than that of polished stems. [4][5][6][7][8][9] This contradiction between biomechanical theory and clinical observation is yet to be resolved.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 In contrast, certain changes in cement fixation and the polymer itself were detrimental and were abandoned. [21][22][23] In recent years there has been a tendency towards an increased use of cementless femoral fixation. 24 The shift in the choice of fixation followed the consistent, durable fixation obtained with uncemented acetabular components, 12,25 ease of implantation, and the poor results of cemented fixation observed with rough and pre-coated stems.…”
mentioning
confidence: 99%
“…24 The shift in the choice of fixation followed the consistent, durable fixation obtained with uncemented acetabular components, 12,25 ease of implantation, and the poor results of cemented fixation observed with rough and pre-coated stems. [21][22][23] Unlike cementless femoral fixation, cemented fixation has numerous advantages: it is versatile, durable and can be used regardless of the diagnosis, proximal femoral geometry, anteversion, and bone quality. It can also act as a local antibiotic delivery system.…”
mentioning
confidence: 99%
“…Als Hauptursache für eine Revisionsoperation (80 % der Revisionen) gibt das Finnish Arthoplasty Register die aseptische Lockerung an (OTTO et al 2006). Bei zementierten femoralen Komponenten beträgt der Anteil aseptisch bedingter Revisionen bis zu 25 % (BEKSAC et al 2006). Eine septische Genese findet sich hingegen nur bei etwa 1 % der Revisionen (LÖHR und KATZER 2005).…”
Section: Zahlen Und Faktenunclassified
“…Sir John Charnley, in Kooperation mit Denis C. Smith, übertrug Ende der 1950er Jahre das aus der Dentalchirurgie bekannte Prinzip der Einzementierung von Implantaten auf die Gelenkendoprothetik und erreichte durch die Verwendung des PMMA-Knochenzementes wesentlich bessere Verweildauern (DI MAIO 2002, SMITH 2005. Schon 1958 erkannte Charnley die Probleme der Schwergängigkeit und des Abriebs von Endoprothesen und entwickelte später das Konzept der low friction arthroplasty (LFA), welches bis heute als Goldstandard gilt und gute Langzeitergebnisse erzielt (HERNANDEZ-VAQUERO et al 2008, GOETZ und HARRIS 1993, BEKSAC et al 2006. Mit der Einführung des HMWPE (High Molecular Weight Polyethylene) im Jahre 1962 gelang Charnley ein weiterer entscheidender Schritt zur Reduktion abriebbedingter Probleme (ELKE 2001).…”
unclassified